Technology and economic performance in the German economy - Horst Siebert; Michael Stolpe (Kiel Institute of World Economics (IfW), 2001)
Germany remains Europe's largest and most diversified source of new technology, but still lags in the fastest growing areas of today's high technology. After World War II, West-German technology policy sought to rebuild the institutions which had supported Germany's leadership in the high-tech industries of the early twentieth century - automobiles, machinery, electrical engineering, chemicals and pharmaceuticals. Increasingly, however, those institutions are seen as failing to respond to new technological stimuli. In addition, Germany's bank-centered capital and inflexible labor markets have long constrained the opportunities of innovative firms for equity-based growth and the incentives for academic brains to set up in private business. Promising changes in technology policy and capital market conditions can be observed only since the mid-1990s.
Keywords: L5; O4; O5; O3; 330; economic growth and aggregate productivity; economywide country studies; regulation and industrial policy; technological change; Technischer Fortschritt; Wirtschaftswachstum; Produktivität; Forschungs- und Technologiepolitik; Innovationspolitik; Industrielle Forschung; Hochtechnologiesektor; Regulierung; Risikokapital; Arbeitsmarktflexibilisierung; Deutschland